2021
DOI: 10.1002/pen.25839
|View full text |Cite
|
Sign up to set email alerts
|

Design of sodium alginate/soybean extract beads loaded with hemp hurd and halloysite as novel and sustainable systems for methylene blue adsorption

Abstract: This work concerns the fabrication of a green, novel, and sustainable system for the efficient removal of methylene blue from aqueous solutions. The proposed system is obtained by using sodium alginate/soybean extract blend reinforced with hemp hurd from agro-waste resources and halloysite nanotubes (HNTs). The ionotropic gelation methodology, using calcium chloride as a crosslinking agent, was easily applied to obtain composite beads. The adsorption studies were carried out up to 24 h using methylene blue as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 88 publications
(115 reference statements)
0
12
0
Order By: Relevance
“…The maximum adsorption capacity, removal efficiency, and regeneration of the obtained SA/Lig beads were compared with bio-based materials in the literature [ 34 , 35 ]. As shown in Table 3 , there are almost no regeneration data for the reported adsorbents [ 7 , 8 , 9 , 10 , 11 ]. Though some of the adsorbents show a much high adsorption capacity at a high initial concentration, the removal efficiency is relatively low.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum adsorption capacity, removal efficiency, and regeneration of the obtained SA/Lig beads were compared with bio-based materials in the literature [ 34 , 35 ]. As shown in Table 3 , there are almost no regeneration data for the reported adsorbents [ 7 , 8 , 9 , 10 , 11 ]. Though some of the adsorbents show a much high adsorption capacity at a high initial concentration, the removal efficiency is relatively low.…”
Section: Resultsmentioning
confidence: 99%
“…Marrakchi reported the adsorption of MB with a cross-linked chitosan/sepiolite composite film [ 8 ], where the maximum monolayer adsorption capacity is 40.986 mg/g, which was obtained for the CS50SP50 under optimal conditions. Bio-based sodium alginate/soybean extract beads reinforced with hemp hurd and halloysite were reported by Viscusi for the adsorption of MB [ 9 ], and the adsorption capacity reached 49 mg/g when adding 35 wt% halloysite. The results of kinetic fitting revealed that the adsorption was based on the chemisorption mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan/sepiolite composite hydrogel were prepared with cross-linking using epichlorohydrin, the CS50SP50 was selected as the best adsorbent for the adsorption of MB, and the monolayer adsorption capacities of this composite is 40.986 mg/g [ 6 ]. Sodium alginate/soybean extract composite hydrogel beads were reported for the removal of MB by Viscusi et al [ 7 ], the adsorption data can be described with a second-order model, and the maximum adsorption capacity is 49 mg/g. Lu et al reported magnetic activated carbon/sodium alginate composite hydrogel beads for the adsorption of MB [ 8 ], and the maximum adsorption capacity is 222.3 mg/g with initial concentration of 700 mg/L, with a removal efficiency of 31.8%.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Sodium alginate, a natural biopolymer extracted from brown seaweed, is mainly composed of alternate blocks of 1-4 linked α-L-guluronic and β-D-mannuronic acid residues. [15] Sodium alginate is a promising material in food, pharmaceutical, cosmetics, and other chemical industries as a stabilizing, thickening, and gelling agent due to its distinguishing properties like biocompatibility, biodegradability, non-toxic nature, and low cost. [16] Nonetheless, it has disadvantages like its strong hydrophilic nature as well as poor mechanical and thermal stability which have restricted its use in comparison to synthetic plastics.…”
Section: Introductionmentioning
confidence: 99%